Proposal for intervention in oral health for children with special needs: partnership between the Academic Dentistry League and Casa Joana (CIPEEX, 2025)
Patients with special needs face significant barriers to accessing dental care, particularly regarding oral health promotion and minimally invasive treatments. In this context, Casa Joana, a community institution that welcomes more than 200 families of children with Down syndrome, autism, and other conditions, is a strategic space for developing outreach initiatives in partnership with the university. The aim is to present the proposed outreach intervention of the Academic League of Dentistry for Patients with Special Needs, in collaboration with Casa Joana, focused on promoting oral health, welcoming families, and analyzing the situational aspects of dental conditions. The project is in the planning phase and will be developed over a day of activities, organized into three areas: (1) oral hygiene workshops with supervised brushing; (2) clinical care using Atraumatic Restorative Treatment (ART); and (3) an educational lecture for parents and guardians, with an emphasis on prevention and oral health maintenance measures. Illustrated and accessible teaching materials will be produced to support understanding. During implementation, the aim is to collect information on oral health conditions and barriers faced by families to inform future care strategies. The aim is to promote immediate improvements in participants' oral hygiene, address simple dental needs, and raise caregivers' awareness of prevention. Furthermore, the program aims to enhance the practical and humanized training of students, bringing the university closer to social needs. This proposal, still in its initial phase, seeks to integrate care, support, and critical analysis of reality, reaffirming the potential of university extension as an instrument of social inclusion, academic development, and transformation.
Keywords: Social Inclusion; Oral Health; Analysis of Situation